Use of a Standardized Patient in Teaching Medical Students to Assess for PTSD in Military Veteran Patients - Jennifer Fabrizio; Kathleen DeNardi; Michael Boland; Jo-Anne Suffoletto (Association of American Medical Colleges, 2017)
Introduction The purpose of this resource is to introduce first- and second-year medical students to the psychiatric concerns of military veterans. The number of veterans receiving care outside of the Veterans Health Administration (VHA) results in many nonVHA medical doctors treating military veterans; thus, it is important that medical students have exposure to military veterans and their unique issues during medical training. A noncombat veteran with posttraumatic stress disorder (PTSD) was specifically chosen for this training to highlight the fact that PTSD can result from a number of different traumatic events that one may experience during military service. Methods The student learners were presented with an hour-long didactic on PTSD, depression, and suicide in military veterans. They subsequently engaged in an hour-long simulation with a standardized patient who was trained in the symptom presentation of PTSD. Each student in the class had an opportunity to complete a medical interview with the standardized patient (SP) and receive feedback from both their peers and the SP. The student learners then evaluated the learning experience. Results Feedback for the course was overwhelmingly positive. The average response to the quality of the presentation question was 4.83 out of 5 (with 1 = poor; 5 = outstanding). Discussion The results indicate that using SPs is a valuable learning modality for teaching medical students about psychiatric concerns in the veteran population.